Tositumomab and Iodine I 131 Tositumomab (Bexaar) - Srinivasan, A. (AJNR Am J Neuroradiol, 2011)
Tositumomab and iodine I 131 tositumomab (Bexaar) therapeutic regimen targets monoclonal antibodies against the CD20 antigen expressed in non-Hodgkin lymphoma. This article reviews the mechanism of action and clinical indications for this regimen.